The Improving Students' English Speaking Skills by Using the Roll Play Method: English - Septiana Wandira; Muhammad Adib Efendi (JOEY: Journal of English Ibrahimy, 2023)
This study is conducted to develop students speaking skills of eighth-grade students of Class VIII A SMP Muhammadiyah 2 Way Panji east Lampung through role-play activities. In this study, the researcher used a classroom action research (CAR) method using a Kurt Lewin design which consisted of planning, acting, observing and reflecting. In this classroom action research, the researcher uses two cycles where each cycle consists of two meetings. Based on the results of research conducted by researchers, the application of role play in the classroom is very popular with students, this is based on the results of the questionnaire 85,99% into very strong categories. In addition, students also experienced a significant increase from before the application of role play, this was proven by the results of the students' scores during classroom action research, namely pre-test 61.58, post-test 1 73.32, post-test 2 79.22.